THE INFLUENCE OF THE PBL LEARNING MODEL ON PROBLEM-SOLVING SKILLS IS REVIEWED FROM THE LEARNING STYLE OF STUDENTS ON THE EARTH STRUCTURE MATERIAL IN GRADE VIII JUNIOR HIGH SCHOOL - Remantoro, Rizal; Zahrotin , Anis; Anfa , Qurrotul (PT. Antis International Publisher, 2024)
This study aims to determine the differences in the influence of problem-based learning (PBL) models on problem-solving skills in terms of students' learning styles carried out in class VIII of SMPN 1 Geneng. The method used in this study is quantitative. The sampling technique in this study is random sampling which will later be taken two classes as experimental classes and control classes. The sample of this study was class VIIIG and class VIIIH with 32 students in class VIIIG as experimental samples and 33 students in class VIIIH as control classes with a population of 268 class VIII students. The study used several instruments collected through problem-solving skills questionnaires, learning style questionnaire sheets, observation sheets, teacher interview sheets, and problem-solving skills test instruments before and after the test. In this study the data collection technique used was ANOVA with the results of this study indicate that the problem-based learning (PBL) model affects students' problem-solving abilities. Students' problem-solving skills are influenced by their learning styles. The test results showed a Sig value level of 0.80> 0.05, this indicates that H0 is rejected and Ha is accepted. So it can be concluded that the learning model (PBL) has a different influence on problem-solving skills in terms of students' learning styles on the material on earth structure in class VIII of SMPN 1 Geneng.